Weight Dependent Convolution on Beurling Spaces and Multipliers - Issa, Abudulaï; Mensah, Yaogan (Sarajevo Journal of Mathematics, 2024)
In this paper, some properties of a generalized translation operator are obtained. A weight dependent convolution product on Beurling spaces is studied. A convolution theorem related to a weight Fourier transform is obtained. Multipliers for the pair $(\mathcal{L}_{ω}^{1}(G),\mathcal{L}_{ω}^{p}(G))$ are introduced.